Microbial resilience to drying-rewetting is partly driven by selection for quick colonizers. (April 2022) - Hicks, Lettice C.; Lin, Simon; Rousk, Johannes
Abstract: Rewetting dry soil induces enormous changes in microbial growth and biogeochemistry. Upon drying-rewetting (D/RW), bacteria have been shown to exhibit two different responses: (1) a more resilient response where bacteria start growing immediately with a quick recovery after rewetting and (2) a less resilient response where there is a pronounced lag-period before bacterial growth starts to increase exponentially. A shift towards a more resilient bacterial growth response has previously been shown to be induced by exposing soils to repeated cycles of D/RW. Here, we test the hypothesis that this response is driven by selection for a bacterial community with traits for quick colonization of labile carbon (C) resources made available upon D/RW. To do so, we compared the responses of soils that had been exposed to either (i) three cycles of D/RW, (ii) three pulses of glucose addition to moist soil or (iii) three pulses of litter addition to moist soil, before all soils were subjected to a D/RW event where bacterial growth, fungal growth and respiration rates were monitored. As expected, exposing the soil to a series of D/RW events resulted in a more resilient bacterial growth response, as well as a faster recovery of fungal growth. Pre-treating the soils with pulses of glucose accelerated the recovery of bacteria after D/RW, but did not select for a bacterial resilience that could match the pre-treatment with exposure to D/RW. Pre-treatment with pulses of litter showed a trend for an accelerated recovery of bacterial growth to D/RW, but to a lesser extent than that induced by pulses of glucose. In contrast, pre-treatment of soil with either pulses of glucose or pulses of litter both led to a faster recovery of fungal growth following D/RW, matching that induced by repeated D/RW cycles. These results suggest that selection for quick colonizers partly explains the shift to a more resilient microbial response to repeated cycles of D/RW, accounting for ca. 60% increase in bacterial resilience and 100% of the increase in fungal resilience compared that induced by repeated D/RW cycles. Highlights: Repeated drying-rewetting (D/RW) cycles accelerated the recovery of bacterial and fungal growth Microbial recovery after D/RW was also accelerated in soils pre-treated with labile C For bacteria, labile C additions accelerated recovery by ca. 60% compared to repeated D/RW cycles For fungi, the accelerated recovery matched that induced by repeated D/RW cycles